"There Were Females That Danced Too": Uncovering the Role of Women in Breaking History. Issue 2 (August 2020) - Aprahamian, Serouj
Abstract : The dominant narrative regarding breaking history is that the dance developed as an "exclusively male" expression of inner-city "machismo." In this study, I challenge this narrative by bringing in the voices of breaking's often-neglected founding practitioners. By juxtaposing primary testimonies with mainstream representations, I aim to show how women have histoirically played a critical role in the dance, and how hegemonic discourse has obscured our understanding of hip-hop's beginnings. I also consider how uncovering the role of women in breaking's history reframes prevailing conceptualizations of its gender performance.